Women’s work–family conflict and its consequences in commuter marriages: The moderating role of spouses’ family commitment in a dyad analysis - Wu, Hsin-Pei; Wang, Yu-Mei (Frontiers in Psychology, 2022)
This study aims to explore the relationship between work-family conflict and its consequences on job, family, and marital satisfaction among stay-at-home wives of commuter couples by testing the moderating effect of commuters’ family (parental, marital, and household) commitment. The phenomenon of commuter marriages is detectable among well-educated and employed couples in modern society. The study collected dyadic data from 120 dual-earner and noncohabitating couples by using convenience sampling. The analytical approach of the Actor-Partner Interdependence Model was adopted. The results revealed that stay-at-home wives perceived more job dissatisfaction due to work-to-family conflicts and perceived more job, family, and marital dissatisfaction caused by family-to-work conflicts. Moreover, the partner moderating effect of the commuters’ family commitment as spouse support reversed the negative relationship between stay-at-home wives’ family-to-work conflicts and family satisfaction.